Effect of artificial weathering on physical and mechanical properties of wood - de Moura Aquino, Vinicius Borges; Bertolini, Marilia Silva [UNESP]; de Morais, Cesar Augusto Galvão [UNESP]; Almeida, Tiago Hendrigo; Almeida, Diego Henrique; Lahr, Francisco Antonio Rocco; Christoforo, André Luis (FapUNIFESP (SciELO), 2021)
– When wood is exposed outdoors, a combination of chemical and mechanical factors and solar radiation contribute to what is described as weathering, being the main degradation agent in this environment. This paper aims to investigate the effect of artificial weathering on mechanical and physical properties of Eucalyptus sp. and Cupiúba (Goupia glabra) woods simulating natural weathering effects. Samples were aged in UV radiation chamber with humidity and temperature control for 100, 200, 300 and 400 hours, considering aging cycles according to ASTM G154 (2006). Wood properties investigated were Conventional value of strength in static bending (fM), Modulus of elasticity in static bending (EM), strength in compression parallel to grain (fc0) and Janka Hardness (fH) according to ABNT NBT 7190 (1997). Effects of artificial weathering on wood properties were evaluated by statistical analysis at 5% significance level. Most of the wood properties investigated did not present significant changes with the aging performed, however, it was noted a decrease in the absolute values of the wood properties absolute values during the aging process. Only fH of Cupiúba wood aged for 100 and 200 hours presented significative performance loss at the significance level considered, which can be related to changes on the wood surface due to weathering exposure.
Efeito do envelhecimento artificial nas propriedades físicas e mecânicas da madeira
Keywords: Artificial weathering; Eucalyptus sp; Goupia glabra